The Relationship Between Pregnancy Intention and Childhood Adversity, Pregnancy Happiness and Breastfeeding Behavior - Kurt, Nuray; Demirelli, Ayşegül; Sabanci Baransel, Esra; Barut, Sümeyye (Inonu University, 2025)
This study was conducted to determine the relationship between pregnancy intention and childhood adversity, pregnancy happiness and breastfeeding behaviour. The descriptive study was conducted in two phases in a hospital in eastern Turkey between November 2022 and October 2023. In the first phase, 316 pregnant women who met the inclusion criteria were reached. Mothers who could not be reached in the 6th postnatal month and those with health problems that might affect breastfeeding were excluded from the study and the study was completed with 216 participants. The data of the study were collected using the Introductory Information Form, Pregnancy Intention Determination Form, Pregnancy Happiness Determination Form, the Adverse Childhood Experience Turkish Form (ACE-TR) and Postpartum Breastfeeding Behaviour Determination Form. It was determined that there was a positive correlation between pregnancy intention and pregnancy happiness (r=.597; p<0.000), and a negative and significant correlation between the categorical scores of the Childhood Negative Experiences Scale (r=-.372; p<0.000), family type (r=-.071; p<0.000), and parity (r=-.373; p<0.000). According to the results of the study, it was determined that the participants who did not want/unplanned pregnancy had less pregnancy happiness and were more exposed to negative childhood experiences, while there was no relationship between pregnancy intention and the time of first breastfeeding. As a result, it was found that participants who did not want/unplanned their pregnancy had less pregnancy happiness and were more exposed to negative childhood experiences, and it may be recommended that these parameters should be considered as part of standard prenatal care. © 2025, Inonu University. All rights reserved.
GEBELİK NİYETİ İLE ÇOCUKLUK ÇAĞI SIKINTILARI, GEBELİK MUTLULUĞU VE EMZİRME DAVRANIŞI ARASINDAKİ İLİŞKİ
Keywords: Breastfeeding; Childhood adversity; Happiness; Pregnancy intention